Analisis Bottleneck pada Produksi Lemon Kering dengan Metode Value Stream Mapping dan Fish Bone Diagram - Hurun'in; Indro Prakoso; Megah Bintang Samudro; Ari Andriyas Puji (Fakultas Teknik UMRI, 2024)
In production and project management, a bottleneck is a disruption of one process in the process chain, so that its limited capacity reduces the capacity of the entire chain. One of the companies in Indonesia that operates in the agricultural industry and produces dried lemons is PT. Semesta Agro Indonesia. At PT. Semesta Agro Indonesia, frequent imbalances in production trajectories were detected. This happens because the dry lemon production line has a queue of material that blocks the production flow. This research was conducted to identify the causes of bottlenecks that occur in the dry lemon production process at PT. Semesta Agro Indonesia. The research results showed that lemon production experienced a bottleneck at the drying and slicing workstations, with a total time in each department of 15,529 seconds and 7,778 seconds, and 5 unnecessary activities were found with a total time of 1844 seconds (30 minutes and 44 seconds). Once an activity is found that does not add value, it is necessary to eliminate it in the process. After eliminating several non-value-added activities, the cycle time, which was previously at 35,679, fell to 33,835 seconds, or a decrease of 30 minutes and 44 seconds